2019
DOI: 10.1155/2019/9651915
|View full text |Cite
|
Sign up to set email alerts
|

QoS Strategies for Wireless Multimedia Sensor Networks in the Context of IoT at the MAC Layer, Application Layer, and Cross-Layer Algorithms

Abstract: Wireless multimedia sensor networks (WMSNs) have got capacity to collect both scalar sensor data and multidimensional sensor data. It is the basis for the Internet of things (IoT). Quality of service (QoS) pointers like energy efficiency, reliability, bit error rate, and latency can be helpful in data collection estimation over a network. In this paper, we review a number of QoS strategies for WMSNs and wireless sensor networks (WSNs) in the IoT context from the perspective of the MAC and application layers as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The work in Reference 29 proposed a smart‐contract based blockchain architecture for effective and secure data communication. Better QoS strategies mentioned in Reference 30 can be utilized to enhance the IoT network's performance further. It is observed that the AR‐MAC [17:27] protocol outperforms other protocols in terms of QoS performance and thus must be used for the deployment of efficient IoT networks.…”
Section: Literature Surveymentioning
confidence: 99%
“…The work in Reference 29 proposed a smart‐contract based blockchain architecture for effective and secure data communication. Better QoS strategies mentioned in Reference 30 can be utilized to enhance the IoT network's performance further. It is observed that the AR‐MAC [17:27] protocol outperforms other protocols in terms of QoS performance and thus must be used for the deployment of efficient IoT networks.…”
Section: Literature Surveymentioning
confidence: 99%
“…QoS is the measurement of the general performance of any service, mainly the performance seen by the users of the service [36][37][38]. Owing to the widespread usage and application of IoT services in our daily life situations, the cost of IoT devices should be low without compromising the level of QoS.…”
Section: Quality Of Service In Internet Of Thingsmentioning
confidence: 99%
“…Tere are several uses for evolving wireless sensor networks (WSNs) in business, education, commuting, infrastructure, and protection [1]. Massive, widely dispersed sensing gadgets having data management capabilities, sensors, actuators, energy harvester devices, various forms of memory, radio signal-based transmitters, and receivers are all included in WSNs [2][3][4]. Such networked devices are placed across a sizable operational region to acquire data by detecting or monitoring the testbed.…”
Section: Introductionmentioning
confidence: 99%